Solid waste management scenarion and emerging technologies / Nor Eeda Ali and Nurain Mohd Talmizi - Ali, Nor Eeda; Mohd Talmizi, Nurain (UiTM Press, 2024)
Cities are fertile ground for science and technological innovation, economic growth, acculturation and for overall individual creativity. However, cities are also places where myriad of problems ranging from pollution, environmental degradation, indiscriminate dumping of waste, crime, unemployment just to mention but a few, are concentrated. Environmental conservation anywhere is incomplete if it lacks efficient solid waste management. The more industrialized and commercialized a city is, the greater the solid waste challenges, as industries and other commercial activities produce a lot of waste. This book is designed to help students, planners, waste management companies, staff of local government and other relevant stakeholders in solid waste management (SWM) understand some of the basic concepts in municipal solid waste (MSW) management. It highlights solid waste management scenarios in developing nations (Malaysia and Thailand) and a developed nation (United States of America). Also, how emerging technologies (smart waste technologies) have been deployed in solid management to address some of the challenges faced with the traditional method of waste management are examined. By the time the reader is through with the book, it is expected that his /her knowledge on the best practices in solid waste management would be enhanced.